Social science research methods and statistics from an Islamic perspective - Alias, Alizi (2005)
The objective of this paper is to provide an Islamic perspective on social science research methods and statistics. This is a theoretical paper bases on reviews of primary sources (al-Qur’an and Hadith) and secondary sources (books and papers) of Islamic and social science (particularly psychology) literature. First, the paper will provide an Islamic overview of the concept of social science research in Islam and compare it with the concept of research in Islamic discipline such as `aqidah, fiqh, and akhlaq. Second, the paper will outline the objectives of social science research including both basic and applied research and their relation to our existence as human being. Third, the paper will evaluate some of the social science research methods and evaluate them from both scientific and religious Islamic perspective. The methods reviewed in this paper are experimental method, correlational method, survey method, case-studies method, natural observation and a few lesser known qualitative methods. Fourth, a related research issue called sampling is also discussed together with some evidence from Islamic literature especially the issue of representativeness in sampling. Fifth, the dilemma faced by researchers in ethical issue will also be discussed with input from Islamic perspective. Finally, a brief description of the importance of statistics in Islam is given to show its basic roles such as organizing knowledge, and applied role such as making decision. All Islamic evaluation will be based on Al-Qur’an, Hadith, Biography of Prophets, various Islamic disciplines, and practices of early Muslim scholars. Finally, the paper concludes that social science research method can help us fulfil our role as servants of Allah (`ibadah role) and as vicegerents of Allah (khilafah role).